2013
DOI: 10.17058/signo.v38i0.4554
|View full text |Cite
|
Sign up to set email alerts
|

Compreensão da leitura e consciência textual nos anos iniciais

Abstract: ___________________________________________________________________ RESUMOAs dificuldades de compreensão da leitura nos anos iniciais são evidenciadas pelas diversas avaliações oficiais. Diante dessas evidências estatísticas e das obtidas por meio de pesquisas acadêmicas e de observações da atuação das crianças no cotidiano escolar, há o reconhecimento da situação como um problema que exige aprofundamento e busca de soluções. A Psicolinguística vem dando sua contribuição, especialmente no que se refere ao pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
1
2
0
8
Order By: Relevance
“…These results corroborate those found by Block, Parris, Reed, Whiteley, and Cleveland (2009), Lai et al (2009), andPereira andGuaresi (2014), who reported superior reading comprehension performance in students submitted to a pedagogical approach that used facilitation strategies such as specific and explicit reading comprehension classroom activities that were carried out by the teacher, like the intervention programs proposed in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results corroborate those found by Block, Parris, Reed, Whiteley, and Cleveland (2009), Lai et al (2009), andPereira andGuaresi (2014), who reported superior reading comprehension performance in students submitted to a pedagogical approach that used facilitation strategies such as specific and explicit reading comprehension classroom activities that were carried out by the teacher, like the intervention programs proposed in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…These last mentioned authors argued that reading comprehension skills in higher education can indicate whether or not the students had a good quality scientific and technical learning. Thus, according to Pereira (2013), these difficulties should be considered a major problem requiring effective solutions. The interest in solving reading comprehension difficulties has led researchers worldwide to carry out studies on intervention activities.…”
Section: Vlo Cunha and Sa Capellinimentioning
confidence: 99%
See 1 more Smart Citation
“…Na concepção de aprendizagem de leitura proposta por Pereira (2010;2012), como referido no item 2 deste artigo, a atividade de escrita deve partir do mesmo gênero textual trabalhado. Ou seja, as atividades de compreensão leitora exigem uma exploração textual consciente, onde os aspectos linguísticos necessitam ser amarrados a partir do texto e do gênero em questão para a construção de sentido.…”
Section: Implicações Pedagógicasunclassified
“…Para tanto, na área da PL, respaldamo-nos em autores como Smith (1991;1999), Solé (1998) e Giasson (2000); dentre os brasileiros, figuram Leffa (1996), Koch e Elias (2008), Kato (1990) e Pereira (2013). No que concerne à AD, contamos com Pêcheux (1997;2008), Charaudeau e Maingueneau (2014) e Orlandi (1987Orlandi ( , 2008, entre outros.…”
unclassified